Strong Summability of Fourier Transforms at Lebesgue Points and Wiener Amalgam Spaces. (2nd September 2015) - Weisz, Ferenc
Abstract : We characterize the set of functions for which strong summability holds at each Lebesgue point. More exactly, iff is in the Wiener amalgam spaceW ( L 1, l q ) ( R ) andf is almost everywhere locally bounded, orf ∈ W ( L p, l q ) ( R )     ( 1 < p < ∞, 1 ≤ q < ∞ ), then strongθ -summability holds at each Lebesgue point off . The analogous results are given for Fourier series, too.